AIRCRAFT HIJACKING: A LEGAL PERSPECTIVE - Agus Pramono (Faculty of Law, Universitas Diponegoro, 2014)
According to International Law, the aircraft crime which is often called as “aircraft hijacking” is considered as one of the crimes against humanity. It is totally condemned by international community because the impact of this crime devastates the humanity values, threatens lives, and destroys belongings. The motives underlines this crime may be derived from personal motive, hostage taking, political reason or being refugee. It is the state who has the full responsibility, based on international law, to resolve the case of aircraft hijacking. The effort to resolve this aircraft hijacking can be done through international networks, bilateral agreement and the extradition of those who commits aircraft hijacking. Keywords : Aircraft Hijacking, States Responsibility. Kejahatan penerbangan merupakan salah satu tindak pidana yang dalam Hukum Internasional sering disebut “Aircraft Hijacking”. Kejahatan penerbangan tersebut menurut Hukum Internasional merupakan salah satu kejahatan kemanusiaan. Kejahatan penerbangan tersebut oleh komunitas internasional sangat dikutuk karena menghancurkan nilai-nilai kemanusiaan, mengancam jiwa manusia dan merusak barang dan harta benda. Bahwa motivasi tindakan kejahatan penerbangan meliputi motif yang bersifat : pribadi, penculikan, politik dan pengungsian. Dalam rangka penanggulangan tindakan kejahatan penerbangan, berdasarkan hukum internasional, Negara mempunyai tanggung jawab penuh untuk mengatasinya. Upaya penanggulangan dapat dilakukan antara lain melalui kerjasama internasional dan ekstradisi pelaku kejahatan pembajakan udara. Kata kunci : Kejahatan Penerbangan, Pertanggungjawaban Negara.